2021
DOI: 10.1016/j.afjem.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute fever in children: Consensus recommendations for community and primary healthcare providers in sub-Saharan Africa

Abstract: Fever is one of the most common reasons for unwell children presenting to pharmacists and primary healthcare practitioners. Currently there are no guidelines for assessment and management of fever specifically for community and primary healthcare workers in the sub-Saharan Africa region. This multidisciplinary consensus guide was developed to assist pharmacists and primary healthcare workers in sub-Saharan Africa to risk stratify and manage children who present with fever, decide when to refer, and how to advi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 93 publications
0
29
0
Order By: Relevance
“…Overuse of antibiotic therapy is an important clinical problem, which increases the rates of microbial resistance ( 41 , 42 ). New guidelines and studies continue to be developed to standardize the symptomatic and causal treatment of respiratory tract infections ( 6 , 12 15 , 43 , 44 ). Data on the use of a delayed antibiotic prescribing strategy for respiratory tract infections have shown that it significantly reduces the frequency of antibiotic use, with no negative effects in terms of an increased number of complications being associated with this treatment approach ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overuse of antibiotic therapy is an important clinical problem, which increases the rates of microbial resistance ( 41 , 42 ). New guidelines and studies continue to be developed to standardize the symptomatic and causal treatment of respiratory tract infections ( 6 , 12 15 , 43 , 44 ). Data on the use of a delayed antibiotic prescribing strategy for respiratory tract infections have shown that it significantly reduces the frequency of antibiotic use, with no negative effects in terms of an increased number of complications being associated with this treatment approach ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also ensures the effective elimination of pathogenic microbes and controls the diseases that they cause (4,10,11). Due to the widespread abuse and misuse of antibiotics, many global and local guidelines for their proper use have been developed (1,5,6,(12)(13)(14)(15). The rational use of antibiotics should lead to the rapid and complete elimination of pathogenic bacteria, with minimal adverse effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the theory, an accurate way of measuring body temperature is to use a thermometer by placing it in several parts of the body including the armpits, mouth, and rectum (El-Radhi et al, 2019;Potter et al, 2015). However, the safest and most accurate place for measurement is the armpit (Green et al, 2021). From these results, it can be concluded that most respondents already know and understand the most accurate way to measure body temperature, namely with a thermometer placed in the armpit as the safest place to measure temperature, but there are still respondents who measure by touching the forehead due to one of them from lack of information.…”
Section: Knowledge Of Parents In Performing Hyperthermia First Aid In...mentioning
confidence: 99%
“…Acute febrile illness (AFI) is defined as a sudden rise in the body temperature above 38 • Celsius (100.4 degrees Fahrenheit) for 2-14 days duration without any specific etiology. 1 AFI is a significant cause of morbidity and mortality in developing countries. AFI is India's most common cause of hospitalization.…”
Section: Introductionmentioning
confidence: 99%